Is the trend in new introductions of marine non-indigenous species a reliable criterion for assessing good environmental status? Τhe case study of Greece - ZENETOS, ARGYRO; KARACHLE, PARASKEVI K.; CORSINI-FOKA, MARIA; GEROVASILEIOU, VASILIS; SIMBOURA, NOMIKI; XENTIDIS, NIKOLAS JASON; TSIAMIS, KONSTANTINOS (Mediterranean Marine Science, 2020)
This study presents the updated status of marine non-indigenous species (NIS) distribution in Greece and investigates trends in new NIS introductions, at both national and subnational level, during 1970-2017. The overall picture shows an increase in new introductions from the 1970s to 2017. The number of unaided introduced species (mainly Lessepsian immigrants) followed an upward trend in the South Aegean Sea until 2017. Similarly, the number of NIS associated with transport-stowaway (NIS introduced mainly via ballast and boat hulls) followed an upward until 2017 in the South Aegean Sea, but also in the Hellenic Levantine coasts. However, these results are greatly affected by a monitoring bias, which appears to be the main factor influencing the number of new NIS introductions reported from Greece and its subnational areas. This monitoring bias, as well as the continuous influx of Lessepsian NIS into the Aegean Sea, constitutes a challenge for Greece as regards setting exact boundaries for areas with or without Good Environmental Status (GES), based on Descriptor 2, primary criterion C1 (D2C1), of the Marine Strategy Framework Directive (MSFD). Dedicated monitoring of marine NIS should be established and be constant in space, time and across taxonomic groups. Prioritization should be given to hot-spot areas of new NIS introductions, such as ports, aquaculture units and marine protected areas. This should be a prerequisite for applying the primary criterion D2C1 of the MSFD properly, at both national and subnational level. Finally, as regards the implementation of D2C1 of the MSDF and setting exact threshold values, we highlight the need for subregional and regional coordination in the Mediterranean.